2002
DOI: 10.1002/1521-4141(200208)32:8<2255::aid-immu2255>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic analysis of the murine CD4-related glycoprotein, CD223 (LAG-3)

Abstract: CD223 (LAG‐3) is an activation‐induced cell surface molecule, structurally similar to the T cell coreceptor CD4, that binds MHC class II molecules with high affinity. Little is known about theexpression and function of murine CD223. Here, we show that mRNA expression is restricted to the thymic medulla, splenic red pulp and sparse cells in the adult brain cortex. In contrast, surprisingly high expression was seen in defined tracts at the base of the cerebellum and in the choroid plexus of day 7 postnatal brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
189
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(199 citation statements)
references
References 35 publications
10
189
0
Order By: Relevance
“…In agreement with previous results (26), flow cytometric analysis revealed that Ͼ90% of LAG-3-expressing cells belonged to the CD4 ϩ CD25 Ϫ CD45RB low population (hereafter called CD4 ϩ CD25 Ϫ LAG3 ϩ cells) (Fig. 1A).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous results (26), flow cytometric analysis revealed that Ͼ90% of LAG-3-expressing cells belonged to the CD4 ϩ CD25 Ϫ CD45RB low population (hereafter called CD4 ϩ CD25 Ϫ LAG3 ϩ cells) (Fig. 1A).…”
Section: Resultssupporting
confidence: 92%
“…Ectopic expression of LAG-3 conferred regulatory activity to naïve T cells (25). Interestingly, LAG-3 protein was hardly detected on the cell surface of CD4 ϩ CD25 ϩ T cells but was expressed by a sizable population of CD4 ϩ CD25 Ϫ T cells (26). We have found that IL-10-secreting CD4 ϩ CD25 Ϫ LAG3 ϩ T cells show a significant regulatory activ-ity in vivo and characteristically express Egr-2.…”
Section: Regulatory T Cells (Tregsmentioning
confidence: 76%
“…1A, the G15, G37 and G40 Ab, as representatives of a large panel (at least 6 different epitopes are recognized by 12 mAb), stain activated T cells from normal but not from LAG-3 knockout (ko) mice. In activated splenocyte cultures, LAG-3 was upregulated on day 1 and reached plateau on day 3 of activation, consistent with previous observations [8]. In addition, LAG-3 expression was consistently 2.0-2.5-fold higher on CD8 + than CD4 + T cells (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Murine LAG-3 transcripts were found in the spleen, thymus and brain. A very small percentage of ab T and NK cells in naive mice express LAG-3, whereas a significant percentage of cd T cells show LAG-3 expression [8].…”
Section: Introductionmentioning
confidence: 97%
“…Because the TCR on antigen-specific T cells is actually down-regulated after activation (27), it is possible that other MHC-II interacting molecules are involved in the MHC-II cross-linking. Surface expression of the MHC-II binding protein LAG-3 is dramatically enhanced during CD4 T-cell activation (28,29); however, preliminary experiments revealed that LAG-3-deficient OT-II T cells also promoted MHC-II degradation in DCs. The TCR and CD4 are also likely candidates for MHC-II ligands; however, analysis of conjugates between MHC-II antigen-specific T cells lacking CD4 and antigen-loaded DCs is not technically possible.…”
Section: Cross-linking Of Mhc-ii Induces Internalization Of Both Relementioning
confidence: 99%